The effect of vitamin D supplementation on the muscle damage after eccentric exercise in young men: a randomized, control trial. Issue 1 (11th November 2020) - Pilch, W.; Kita, B.; Piotrowska, A.; Tota, Ł.; Maciejczyk, M.; Czerwińska-Ledwig, O.; Sadowska- Krepa, E.; Kita, S.; Pałka, T.
Abstract: Background: Vitamin D contributes to the optimal functioning of muscles. This study was designed to determine the modulating effect of vitamin D supplementation on the degree of muscle cell damage caused by eccentric exercise in young men. Methods: 60 male volunteers (20–24 years old) taking part in this study were divided in two groups - with suboptimal (S) and optimal (O;) 25(OH)D plasma levels. These groups were randomly subdivided into groups with vitamin D supplementation (experimental: SE and OE) and controls (SC and OC). Before the supplementation (Test I) and after 3 months (Test II), participants were subjected to two rounds of eccentric exercise tests on a declined treadmill (running speed corresponded 60% VO2peak determined in each subject in incremental exercise test). During each test, blood samples used for determination of 25(OH)D, Il-1β, myoglobin (Mb) levels and CK, LDH activity were taken at three timepoints: before the test, 1 h and 24 h after it ended. After distribution normality testing (Saphiro-Wilk test), statistical analyses were performed. Non-parametric: Kruskal-Wallis test and the Wilcoxon test were applied, and the Dunn-Bonferroni test as a post-hoc test. Results: In all groups, after 3 months, higher concentrations of 25(OH)D were indicated (SE p  = 0.005; SC p  = 0.018; OE p =  0.018; OC p  = 0.028). SE and SC groups showed higher baseline concentrations of Il-1β and significantly higher concentrations of this interleukin after 1 h compared to groups with an optimal 25(OH)D level. After supplementation, the SE group reacted with a similar jump in concentration of Il-1β as the OC and OE groups. The change after 1 h after exercise in Test II was significantly different from that from Test I ( p  = 0.047) in SE group. Lower Mb concentrations indicated 1 h after exercise in Test II for SC and SE groups were indicated. CK activity did not differentiate the studied groups. Plasma calcium and phosphate disorders were also not indicated. Conclusions: The study has shown that vitamin D doses determined from the plasma concentration of 25(OH)D of individuals to match their specific needs can significantly reduce muscle cell damage induced by eccentric exercise.